2014
DOI: 10.5539/gjhs.v6n4p148
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Determinants of Gestational Weight Gain an Important Predictor of Infant Birth Weight in a Developing Country

Abstract: The study aimed to determine correlates of gestational weight gain and infant birth weight of pregnant women attending antenatal clinics in public primary health care facilities in lfe Central and East Local Government Areas of Osun State, Nigeria. Over 1000 women were recruited during booking and antenatal clinic and followed up till delivery. Chi square was used in the bivariate analysis of association between gestational weight gain, pre pregnancy BMI and demographic characteristics. The correlates of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 13 publications
7
39
1
1
Order By: Relevance
“…Furthermore, our study found about three quarters of participants with a normal pre-pregnancy BMI. This is close to that reported in the Nigerian study [10], but is higher than the 65.4% that was reported in a study conducted in Vietnam [23]. …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, our study found about three quarters of participants with a normal pre-pregnancy BMI. This is close to that reported in the Nigerian study [10], but is higher than the 65.4% that was reported in a study conducted in Vietnam [23]. …”
Section: Discussionsupporting
confidence: 84%
“…The pre-pregnancy BMI of the participants was close to what was reported in Nigeria [10] but was lower than what was reported in another study in Nigeria and also in Brazil [20, 21]. Our low BMI could be explained by the fact that our study enrolled only women who were pregnant for the first or second time and the majority were relatively young, mean age of 20.9 years.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Factores como la paridad (20)(21)(22), la edad (20,23), el nivel educativo (23), la etnia o raza (24,25), el IMC pregestacional (19,22) o el tabaquismo (4,26) han sido intermitentemente relacionados con la ganancia de peso gestacional. En nuestra muestra, la edad y el IMC pregestacional se asociaron de forma inversa a la ganancia de peso gestacional.…”
Section: Discussionunclassified